WATERPLANT OF SEAWAGE AND COMPARISON OF THE WITH THE ANALOGUE FLORA (Ustozlar uchun, 2025)
The article presents data on the comparative analysis of biological ponds, sewage treatment plants, which according to its climatic , hydrological and physical- chemical conditions of the environment is different from the other ponds. This article discusses the ecological- floral analysis of natural population of algal ponds used as biological ponds - reservoirs, clarifiers.